The pandemic's effect on a patient cohort with painful polyneuropathy in 2020: A longitudinal study on pain, mood, and everyday life. Issue 50 (16th December 2022) - Kersebaum, Dilara; Sendel, Manon; Fabig, Sophie-Charlotte; Sachau, Juliane; Lassen, Josephine; Rehm, Stefanie; Forstenpointner, Julia; Rümenapp, Johanna; Vollert, Jan; Hüllemann, Philipp; Baron, Ralf; Gierthmühlen, Janne
Abstract : In the early phase of the COVID pandemic 2020, we demonstrated how patients with painful polyneuropathy, against our expectations, did not experience a deterioration of their neuropathic pain. We hypothesized that our assessed measures, that is, pain intensity and characteristics, emotional wellbeing, and everyday life, would deteriorate in the further course of the pandemic according to the phases of disaster management. Thus, the aim of our study was to investigate patients repeatedly under varying pandemic conditions from March until December 2020. Sixty-three patients were investigated with validated questionnaires (brief pain inventory [BPI], neuropathic pain symptom inventory [NPSI], pain catastrophizing scale [PCS], patient-reported outcomes measurement information system [PROMIS] pain interference/sleep disturbance/fatigue/ depression/anxiety, EuroQol 5 dimensions 5 level version [EQ-5D-5L]) and a pandemic-specific, self-designed questionnaire. The data from the beginning of the pandemic with severe restrictions, during summer with loosened regulations and from December 2020 with reinstalled, severe restrictions were compared with an observational design. Patients reported higher pain severity when restrictions were lower. Sleep, mood, and quality of life did not change in the course of the pandemic in the validated measures. Pain interference significantly decreased during the study independent from restrictions. Patients who reported medical disadvantages had a lower quality of life upon EuroQol 5 dimension (EQ-5D) and were significantly more worried about their health. The perception of pain intensity was dependent on pandemic severity. Sleep, mood, and quality of life did not change significantly in validated measures. Continued medical care seems decisive to prevent worsening of pain and quality of life.